Olmesartan Medoxomil Nanomicelle Using Soluplus for Dissolution Enhancement :Preparation, In-vitro and Ex-vivo Evaluation - Rajab, Nawal Ayash; Talal Sulaiman, Halah (Iraqi Journal of Pharmaceutical Sciences, 2025)
The antihypertensive medication olmesartan medoxomil (OLM) is pharmacologically selective angiotensin-II receptor antagonist. Pharmaceutically speaking, OLM is a class II medication (low solubility, high permeability) that is practically insoluble.Due to its extremely poor solubility, which negatively affects its usefulness, oral medication have a low (26%) bioavailability. The current strategy involves generating OLM as a micellar dispersion in the nano range scale utilizing the film hydration process. In order to prepare transparent aqueous formulations, increase drug solubilization, and administer medication orally, Soluplus (SLP) was employed as a micellar nanocarrier.Different SLP concentrations were used to make eight formulations. Micelle size, polydispersity, morphology, encapsulation efficiency and in vitro release testing were used to gauge the micellar system's concentration-dependent characteristics. The systems' particle sizes ranged from 48.9 ±0.98 nm (F8) to 461.3± 5.07 nm (F1), with approved poly dispersity index values. OLM release behavior in vitro from micelles with particle size less than 100 nm against a pure medication aqueous suspension was evaluated. In comparison to pure drug powder suspension, all tested formulas demonstrated a significant increase in drug release at p˂0.05. The chosen formulation was subjected to lyophilization , fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) analysis, transmission electron microscopy (TEM) observation ,stability and ex vivo permeation investigations utilizing the non everted intestinal sac technique. F7 with SLP concentration 1.6% showed higher percentage of drug release with particle size of 51.09 nm. DSC of lyophilized F7 formula showed absence of crystalline state which mean complete encapsulation of drug within nanocarrier .The FTIR revealed no incompatibility between drug and excipient. The results of particle size analysis were analogous to TEM image.The selected formula was stable upon storage and dilution with water.The ex vivo study showed improvement in the permeability of the formulated nanomicelle (NM) and the permeability coefficient was increased more than two time compared to the pure drug dispersion. Accordingly it deduced that formulating OLM-NM based on SLP is a promising strategy. It can improve OLM permeability by two and release.